The factors associated with the knowledge of brushing teeth with fluoridated toothpaste among high school students in Al-Madinah, Saudi Arabia - Kassim, Saba; Alsharif, Alla T. (Frontiers in Oral Health, 2024)
Objective: The use of fluoridated toothpaste (FT) is essential for controlling caries. This analytical cross-sectional study aimed to determine the proportionenumerate number of students who brushed their teeth with fluoridated toothpaste/or do not know the content toothpaste at least once a day and to determine the factors associated with the knowledge of brushing teeth with FT. Methods: An anonymous questionnaire was distributed during the academic year 2019-2020 among 439 high school students. The data collected included sociodemographic characteristics and oral-health-related variables (e.g., brushing teeth, knowledge of the effect of fluoride on caries (KEFC) and dental service utilisation [DSU]). The dependent variable was the knowledge of using FT when brushing teeth (Yes or do not know). Descriptive, bivariate, and logistic regression analysis were performed. Results: The response rate was 98% (n=432) and usable data was 88% (n=385). The median (IQR) age of the students was 16.00 (1) years, and 190 (47%) were males. Eighty eight percent of the students brushed their teeth with toothpaste daily with no knowledge of toothpaste content and only 86 (21.8%) knew the content of the toothpaste used for brushing their teeth i.e., FT. In the bivariate analyses, age, gender, family income, KEFC and DSU were significantly (p<0.05) associated with the knowledge of brushing teeth with FT. The multivariable analyses revealed an association of family income and KEFC with brushing teeth with FT (adjusted odds ratio [AOR]: 1.98, 95% confidence interval [CI]: 1.14-3.43, p = 0.015 and AOR = 6.11, 95% CI: 3.45-10.83, p < 0.001, respectively). Conclusions: While the brushing and use of toothpaste among high school students was common, the knowledge of the content of toothpaste used for brushing teeth was less common and was associated with family income and KEFC.